2018
DOI: 10.20307/nps.2018.24.1.21
|View full text |Cite
|
Sign up to set email alerts
|

The Amelioration Effect of the Ethanolic Extract of Cnidium officinale in Mice with Imiquimod-induced Psoriasis-like Skin Lesion

Abstract: − Psoriasis is an auto-immune skin disease, which is characterized by the excessive generation of plaques on the skin with typically a long-lasting red, itchy and scaly symptoms. Imiquimod, which has been used for the treatment of external genital warts, actinic keratosis, and superficial basal cell carcinoma, induced of psoriasis-like skin disorders with skin erythema and thickness in mice. In the present study, we tried to find the bioactive herbal extract against imiquimod-induced psoriasis-like skin disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The LOD and LOQ are established successfully for each impurity in Imiquimod based on signal-to-noise ratio method (10,11). The results are presented in Table 11.…”
Section: Lod and Loqmentioning
confidence: 99%
See 1 more Smart Citation
“…The LOD and LOQ are established successfully for each impurity in Imiquimod based on signal-to-noise ratio method (10,11). The results are presented in Table 11.…”
Section: Lod and Loqmentioning
confidence: 99%
“…[7][8][9] There has been a suggestive evidence that imiquimod, when applied to skin, leads to the activation of cells of Langerhans, which then migrate to nearby lymph nodes to set off an adaptive immune response. [10] Natural killer cells, macrophages, and B-lymphocytes are the types of cells naturally triggered by imiquimod recent studies suggest that imiquimod exerts its effect through growing levels of the opioid growth factor receptor none. [11] The study revealed that blocking function…”
Section: Introductionmentioning
confidence: 99%